Structure reinforced birnessite with an extended potential window for supercapacitors. Issue 18 (28th April 2020) - Zhao, Yang; Fang, Qin; Zhu, Xiaohui; Xue, Liang; Ni, Mingzhu; Qiu, Ce; Huang, Hao; Sun, Shuo; Li, Shuang; Xia, Hui
Abstract : Structure reinforced birnessite via Cr doping exhibits large capacitance, good rate performance, and outstanding cycle life in an extended potential window. Abstract : Although δ-MnO2 with a layered structure is a promising electrode material for supercapacitors, its poor electronic conductivity and structural instability limit its electrochemical performance. In this work, structure reinforced birnessite with improved electron transfer is developed via Cr doping in δ-MnO2 using hydrothermal synthesis. The Cr-doped δ-MnO2 exhibits significantly improved specific capacitance and cycling stability in an extended potential window (0–1.2 V vs. Ag/AgCl) compared to pristine δ-MnO2 . Specifically, the 2 mol% Cr-doped δ-MnO2 (0.02CrMO) electrode exhibits large specific capacitances of 250 F g −1 at 0.2 A g −1 and 150 F g −1 at 10 A g −1 (∼5 mg cm −2 mass loading) as well as an outstanding capacitance retention of 82.6% after 30 000 cycles. Both calculations and experimental results demonstrate that Cr doping in δ-MnO2 can narrow the band gap, enhance electron transfer, and strengthen the layered structure with suppressed Jahn–Teller distortion, resulting in reduced Mn dissolution and phase transition.